Robust parametric optimization of discrete systems stabilization of ground moving object - Сущенко, О.А. (Proceedings of National Aviation University (archive), 2009)
Features of the discrete stabilizing system robust parametric optimization for the ground vehicle are considered. Method of the studied system sampling is chosen. The chart of algorithm for the ground moving object robust stabilizing system synthesis is suggested and results of the optimal system are represented.